Nikah Gantung in Legal and Social Discourse: The Contestation of Legality between State, Religion, and Custom - Zukhrufil Shadri; Rintia Rintia; Md Shahidur Rahman Shakil (Journal Governance Society, 2025)
ABSTRACT Nikah gantung is a marriage practice that is religiously valid, yet the couple does not live together or fulfill domestic obligations such as financial support. This phenomenon is commonly found in several traditional communities in Indonesia, primarily as an effort to preserve family honor, avoid premarital sex, or due to economic reasons. However, behind this practice lies a serious discrepancy between religious norms, customary law, and state legal regulations—particularly in terms of marriage registration, legal protection, and minimum marriage age. This study aims to critically analyze the tension among religious, customary, and state institutions in defining the legality of nikah gantung. It also explores how the power relations among these three institutions shape the meaning of what constitutes a "valid" marriage, and how this affects the protection of women's and children's rights. The method used is a qualitative literature study with a critical discourse analysis approach. Data were obtained from previous studies on nikah gantung, Islamic family law, civil law, and anthropological research on customary practices. The analysis applies Michel Foucault’s theory of power, particularly the concepts of governmentality, regime of truth, and symbolic discipline. The findings reveal that marriage legality in the context of nikah gantung is not neutral, but rather the result of competing discourses: the state demands administrative certainty, religion emphasizes sacred legitimacy, and customary norms operate through shame and honor. This research concludes with a call for a more integrative, just, and rights-oriented approach to family law that respects cultural diversity.